Low overhead on-demand routing protocol for mobile ad hoc networks - JIANG Guo-xing; YI Ming (Tongxin xuebao)
To improve the performance of flooding,an efficient broadcasting algorithm with constrained flooding was proposed,this algorithm only selected efficient some from all routing packets to forward according to Euclidean Distance.A packet listening method,which could reduce route maintenance overhead and route discovery frequency,was studied,then a local route repair and optimization algorithm,which was based on node height and can repair the failure path due to link breakage,was presented.Furthermore,based on the efficient broadcasting algorithm and local route repair and optimization algorithm,a new on-demand routing protocol,named LOOR（low overhead on-demand routing）,was proposed.The simulation results on ns2 show that LOOR can enhance the route robustness,decrease the average hop count,the route discovery frequency and the routing overhead obviously,and increase the packet delivery ratio.